Acute Nomophobia and Its Psychological Correlates in Adolescents: An Explanatory Sequential Mixed-Methods Approach - AL Maghaireh DF; Shawish NS; Abu Kamel AM; Kawafha M (Dove Medical Press, 2025)
Dua’a Fayiz AL Maghaireh,1 Najah Sami Shawish,2 Andaleeb M Abu Kamel,2 Mariam Kawafha3 1Nursing Faculty, Sulaiman Al Rajhi University, Al Bukayriah, Saudi Arabia; 2Nursing Faculty, Al-Zaytoonah University of Jordan, Amman, Hashemite Kingdom of Jordan; 3Nursing Faculty, Yarmouk University, Irbid, Hashemite Kingdom of JordanCorrespondence: Dua’a Fayiz AL Maghaireh, Nursing Faculty, Sulaiman Al Rajhi University, Al Bukayriah, Saudi Arabia, Email dfm_2013@yahoo.comBackground: Nomophobia is a recent medical term; it is a combination of “no-mobile” and “phobia”. Nomophobia encompasses feelings of fear, anxiety, and discomfort stemming from the absence of a mobile device or the inability to access one, when necessary, as well as the apprehension of disconnection from the digital realm. It’s correlated with many psychological problems.Aim: This study aimed to explore the impact of nomophobia and its psychological correlates, particularly stress, loneliness, and depression, among adolescents.Methods: Explanatory sequential mixed-methods design was used. A sample of 180 students were participated. They completed the Nomophobia Questionnaire, Perceived Stress Scale, Beck Depression Inventory, and UCLA Loneliness Scale, followed by semi-structured interviews with 30 students exhibiting high levels of nomophobia.Results: The study found that the majority of students (76.7%) exhibited high levels of nomophobia, with a higher prevalence among females (78.72%) compared to males (69.76%). Students reported high levels of stress (mean = 32.96, SD = 1.35) and social loneliness (mean = 67.9, SD = 4.17), while depression levels were low (mean = 7.03, SD = 4.1). Female students experienced higher levels of stress and loneliness than their male counterparts. Stress and social loneliness were identified as significant predictors of nomophobia, with positive associations (coefficients: 1.64 and 1.20, respectively) and strong correlations (R² = 0.93 and 0.98, p = 0.01). Depression showed a negative but non-significant association with ...